Modern Homeschooling Trends: An Alternative to Children's Education in the Flexible Era - Baihaqi, Mohammad (Journal of Islamic Elementary Education, 2025)
This study explores the growing trend of modern homeschooling as an alternative educational option in the flexible era. Homeschooling offers a personalized approach to learning, allowing parents to tailor the curriculum and teaching methods to suit their child's individual needs, interests, and learning pace. This research examines the motivations behind parents' decisions to choose homeschooling, the learning processes involved, the challenges faced, and the potential impacts on children's development. Data were collected through in-depth interviews, observations, and documentation from parents, children, and educators involved in homeschooling practices. The findings highlight the advantages of homeschooling, such as flexibility in learning schedules, personalized education, and the development of independence and critical thinking skills in children. However, challenges like limited resources, time management, and social development were also identified. The study concludes that while homeschooling presents numerous benefits, it requires careful planning, adequate resources, and support from the broader community to be fully effective.